Design and implementation of DPFC for multi-bus power system - Vijaya Krishna, B; Venkata Prashanth, B; Sujatha, P (International Journal of Engineering and Technology, 2018)
In current days, the power quality issues in the interconnected power system are mainly happens due to the demand of electricity and utilization of large non-linear loads as well as inductive/capacitive loads. The power quality cries are voltage sag and swell in multi-bus power system (MBPS). In this article studies on a two bus, three bus and five bus power systems using DPFC. In order to eliminate the voltage sag and swell in the MBPS, a distributed power flow controller (DPFC) is designed. The structure of the DPFC consists of three-phase shunt converter and three single series phase converters. Both these converters are arranged in back-back voltage source inverters (VSIs). These converters are controlled with help of the pulse width modulation (PWM) scheme. The feedback controllers and reference signals are derived the PWM for DPFC to magnify the power quality problems in MBPS. The performance of the model is investigated at different loads by making of MATLAB/Simulink model. The simulation results are presented.